Model Of Increasing Purchase Intention Through Influencer Engagement On Social Media - Prasetyo Hartanto (Jurnal Manajerial, 2025)
Background – The advancement of internet technology has influenced shifts in consumer thinking and purchasing behavior. Nowadays, people from diverse demographic groups—including both genders, adolescents, and adults—are increasingly using the internet as a platform for business and marketing activities. Aim –The aims of this study are as follows: (1) To examine whether Perceived Credibility exerts a positive and significant effect on Attitude Toward the Influencer; (2) To investigate the influence of Trust on Attitude Toward the Influencer and determine whether it is both positive and significant; (3) To assess whether Perceived Behavioral Control significantly and positively affects Attitude Toward the Influencer; (4) To explore the extent to which Subjective Norms contribute positively and significantly to Attitude Toward the Influencer; (5) To evaluate whether Perceived Expertise positively and significantly influences Attitude Toward the Influencer; (6) To determine whether Perceived Congruence has a positive and significant relationship with Attitude Toward the Influencer; (7) To analyze the positive and significant impact of Attitude Toward the Influencer on Engagement; (8) To examine whether Attitude Toward the Influencer significantly contributes to Purchase Intention in a positive manner; and (9) To analyze the influence of Engagement on Purchase Intention, with a focus on identifying whether the effect is positive and significant. Design / Methodology / Approach – The methodology of this research use crossesctional and hypothesis testing. Data was collected using questionnaire with the measeurement using Likert scale. The samples of this research are followers Instagrams’s Account of Rinaldi. Findings – The findings of this research demonstrate that: (1) Perceived Credibility exerts a positive and statistically significant effect on Attitude Toward the Influencer; (2) Trust significantly and positively impacts Attitude Toward the Influencer; (3) Perceived Behavioral Control shows a positive and significant relationship with Attitude Toward the Influencer; (4) Subjective Norms positively and significantly influence Attitude Toward the Influencer; (5) Perceived Expertise has a significant and positive effect on Attitude Toward the Influencer; (6) Perceived Congruence significantly contributes to the formation of a positive Attitude Toward the Influencer; (7) Attitude Toward the Influencer significantly and positively influences Engagement; (8) Attitude Toward the Influencer has a positive and significant effect on Purchase Intention; and (9) Engagement positively and significantly affects Purchase Intention. Conclusion – This Study Successfully Addressed All Research Questions Through Hypothesis Testing. Research implication – The findings of this study offer several practical implications that can serve as valuable input for influencers in fulfilling their role as product promoters through personal social media accounts.  Limitations – This study has several limitations. First, the dimensions and measurement items used are limited, as the data were collected from 258 respondents who exclusively follow a single influencer. The sampling is not evenly distributed and does not include followers of Rinaldi’s Instagram account who reside outside Jakarta. Furthermore, the influencer examined in this study is specifically associated with educational products, which limits the generalizability of the findings. Future research may expand the scope by exploring other types of products. Additionally, the issues and contexts explored in this study are subject to change over time and may require further development in response to evolving trends.